Organization Of Children’s Independent Activities In Development Centers In Preschool Educational Organizations - Abdullayev Dilshodbek Yuldashali oglu (European International Journal of Pedagogics, 2025)
This article deals with the organization of children's independent activities in the development centers established in pre-school education organizations, as a result of which children's psychological readiness for school education is determined.